The fate of flavonoids after oral administration: a comprehensive overview of its bioavailability. Issue 22 (22nd July 2022) - Naeem, Abid; Ming, Yang; Pengyi, Hu; Jie, Kang Yong; Yali, Liu; Haiyan, Zhang; Shuai, Xiao; Wenjing, Li; Ling, Wu; Xia, Zhang Ming; Shan, Liu Shan; Qin, Zheng
Abstract: Despite advancements in synthetic chemistry, nature remains the primary source of drug discovery, and this never-ending task of finding novel and active drug molecules will continue. Flavonoids have been shown to possess highly significant therapeutic activities such as anti-inflammatory, anti-oxidant, anti-viral, anti-diabetic, anti-cancer, anti-aging, neuroprotective, and cardioprotective, etc., However, it has been found that orally administered flavonoids have a critical absorption disorder and, therefore, have low bioavailability and show fluctuating pharmacokinetic and pharmacodynamic responses. A detailed investigation is required to assess and analyze the variation in the bioavailability of flavonoids due to interactions with the intestinal barrier. This review will emphasize on the bioavailability and the pharmacological applications of flavonoids, key factors affecting their bioavailability, and strategies for enhancing bioavailability, which may lead to deeper understanding of the extent of flavonoids as a treatment and/or prevention for different diseases in clinics.